O19.2 Pre-exposure prophylaxis and risk compensation: evidence of decreased condom use at three-month follow-up among predominantly gay male participants in the vicprep study. (13th September 2015) - de Wit, JBF; Murphy, DA; Lal, L; Audsley, JM; Roth, N; Moore, R; Tee, BK; Read, T; Wright, EJ
Abstract : Introduction: Pre-exposure prophylaxis (PrEP) decreases HIV risk among uninfected people, but risk compensation may affect prevention benefits. PrEP trials and extensions found no decrease in condom use, but included extensive prevention education. We investigated condom use in the VicPrEP study, the first implementation study of PrEP in routine practice in Australia. Methods: Enrollment commenced in June 2014, with capacity for 115 at risk HIV negative gay/bisexual men, transgender people and heterosexual serodiscordant couples seeking to conceive. Participants are recruited from three GP clinics, one sexual health clinic, and one hospital clinic in Melbourne. Participants consent to using daily Truvada for at least one year, and complete baseline and three-monthly clinical evaluations and self-report behavioural surveys. Results: At 31 March 2015, 92 participants completed baseline surveys, and 76 completed three-month follow-up; all gay/bisexual men (mean age 37.7 years; 67.4% university educated; 75.0% Australian born). In the past three months half had regular partners (Baseline: 48.9%, Follow-up: 55.8%; ns); nearly all had casual partners (Baseline: 90.2%, Follow-up: 88.2%; ns). Mean frequency of intercourse in the past three months remained stable for regular partners (Baseline: 19.0, Follow-up: 18.9; ns), and decreased for casual partners (Baseline: 19.1, Follow-up: 16.0; p = 0.056). Condom use was assessed on a 5-point scale (1 = never, 5 = always), and decreased with regular partners (Baseline: mean 2.0 [SD 1.6], Follow-up: mean 1.7 [SD 1.3]; p = 0.048), and casual partners (Baseline: mean 3.0 [SD 1.3], Follow-up: mean 2.5 [SD 1.4]; p = 0.002). Serosorting, viral load sorting, strategic positioning and withdrawal remained unchanged with regular and casual partners. Conclusion: This is the first study documenting a decrease in condom use amongst HIV-negative gay/bisexual men using PrEP. Findings highlight the potential for risk compensation to reduce benefits of PrEP when implemented in routine practice, if adherence is insufficient. This underscores the continued importance of promoting sexual risk reduction practices, including condom use. Disclosure of interest statement: The VicPrEP study was funded by the Victorian Department of Health and study drug was supplied by Gilead. John de Wit receives research funding from the National Health and Medical Research Council, the Australian Government Department of Health, the NSW Ministry of Health, the Victorian Department of Health, Queensland Health, Western Australian Department of Health, Gay Men's Health SA, ACT Health, Tasmanian Council on AIDS, Hepatitis and Related Diseases, the Netherlands Institute of Public Health and Environment (RIVM), AIDS Fonds, The Netherlands, and UNESCO Bangkok. He has received lecture sponsorship from BMS Australia, is a board member of ACON Health Inc and a member of the Steering Committee of the HIV in Europe initiative. Dean Murphy receives funding from the Australian Government Department of Health and a research grant from the Victorian Department of Health. Luxi Lal has no interests to disclose. Jennifer Audsley has no interests to disclose. Norman Roth has received honoraria for Advisory Boards and/or educational events from ViiV, MSD, Gilead and Bristol Myers Squibb. Richard Moore has received financial assistance for education from Gilead, Viiv and Merck. BK Tee has no interests to disclose. Tim Read works at Melbourne Sexual Health Centre which receives study payments from Gilead. Edwina Wright receives funding from a research grant from NIH, research funding from the Victorian Department of Health and unrestricted research funds from Gilead, Abbott, Janssen Cilag, MSD and Boehringer Ingelheim. She has also received funding that has been used for research purposes only from ViiV, Merck, Gilead, and Abbott for consultancy work, payment for lectures from ViiV and payment for developing educational resources for ViiV, MSD and Gilead.